COVID-19 and Children with Congenital Heart Disease: Pandemic Implication - Mamun, Mohammad Abdullah Al; Hussain, Manzoor; Rima, Rezoana (Dhaka Shishu (Children) Hospital Journal, 2021)
While the global coronavirus crisis worsens, a surprising feature of the disease appears that children might be immune from the worst form of it. Studies suggest that COVID- 19 is more likely to infect older adult men, particularly those with comorbidities. There is only limited data detailing the effects of COVID-19 on the pediatric population. Patients with underlying cardiovascular comorbidities are at increased risk of morbidity and mortality from SARS-CoV-2 infection. Certain adult patients with congenital heart disease (ACHD) and with complex congenital heart disease can be considered as high risk for complications related to COVID-19 infection on the basis of decreased functional reserve. While no study on COVID-19 has been included paediatric patients with congenital heart disease, it stands to reason that patients with congenital heart disease can be considered at higher risk for complications from COVID-19. Given the increased risk for severe COVID-19 in adults with underlying cardiac disease, there is concern that patients with congenital heart disease (CHD) may likewise be at increased risk for severe infection, as they are known to have higher risk for complications with viral illnesses including respiratory syncytial virus and influenza. DS (Child) H J 2020; 36(2): 138-145